DEVELOPMENT OF THE LINGUOCULTURAL COMPETENCE OF FUTURE TEACHERS OF PRESCHOOL EDUCATION INSTITUTIONS AS A PEDAGOGICAL PROBLEM - Inna D. Davydchenko (Alfred Nobel University Publisher, 2019)
The article deals with topical issues of formation of the linguocultural competence of future teachers of preschool education institutions. We believe that for the educator who implements the educational process, linguocultural competence is important, which ensures the effectiveness of the performance of basic professional tasks. Since linguistic and cultural competence is an integrative multi-aspect innovation, it does not occur spontaneously, a targeted formation is needed, which should begin at higher education institutions where future tutors of pre-school education institutions are trained. For students of higher educational institutions who have already mastered systemic linguistic knowledge and developed practical literacy skills according to their personal qualities, the study of linguistic culturology is of great importance. On the basis of the analysis of theoretical sources, the notion of formation of linguistic and cultural competence as a pedagogical phenomenon and linguistic and cultural education as a pedagogical process is most effectively considered in the implementation of several procedures, which include: a) analysis of the concept of "linguistic and cultural competence" in the scientific and pedagogical theory; the emphasis of the main stages and social and historical preconditions of the formation of the researched issue; c) analysis of the evolution of theoretical concepts of linguistic and cultural competence, its relationship with the culture of society, language and the laws of functioning in the historical context on the basis of the highlighted social and historical background. Professional training in pedagogical higher education is preparation for a variety of pedagogical activities in educational institutions of various types and levels. Despite the diversity of the profiles of the teaching profession, they have one thing in common - the preparation of a competent teacher, possessing the necessary theoretical and practical knowledge and skills. However, today it is necessary to draw attention to cultural linguistics in teacher education in order to ensure not only a high level of professional training, but also to raise the "general" level of culture, to study fixation in the language and discursive practice the spiritual and material culture of the people, i.e. the culturally significant information and symbolic ways of material and spiritual awareness of the world preserved in the collective memory of a people of a certain ethnic group, reproduced in their ideas, patterns of thinking and behavior, with ethical and aesthetic values, norms, customs, rituals, myths, beliefs, prejudices, everyday life.